Primary progressive aphasia: a review of neuropsychological tests for the assessment of speech and language disorders. Issue 12 (2nd December 2017) - Battista, Petronilla; Miozzo, Antonio; Piccininni, Marco; Catricalà, Eleonora; Capozzo, Rosa; Tortelli, Rosanna; Padovani, Alessandro; Cappa, Stefano F.; Logroscino, Giancarlo
ABSTRACT: Background : Speech and language impairments are the key clinical feature in several neurodegenerative disorders and primary progressive aphasia (PPA) is the syndrome where they are the prominent features. Their accurate and early identification may increase the diagnosis in the clinical setting. This approach may allow a better discrimination between the different neurodegenerative disorders and the PPA variants, i.e., nonfluent, semantic, logopenic. Aims : The aim of this work is twofold: (1) to provide an overview of the available neuropsychological tests for the diagnosis of PPA and/or for the differentiation among the PPA variants and (2) to evaluate the methodological quality and the psychometric characteristics of these tests. Methods & Procedures : This review was conducted following PRISMA guidelines. Search terms were chosen based on the research questions and used in a search in two databases. Then, inclusion criteria were formulated and papers meeting the criteria were reviewed. The methodological quality of the studies was evaluated examining the following items: (1) blindness of personnel, (2) consecutive inclusion of patients, and (3) representativeness of the sample. Outcomes & Results : A total of 907 papers have been selected from the databases, and 9 of them were included in this review. Among these, three tests aimed to differentiate between PPA variants, two tests were designed for the assessment of language disorders in PPA patients, and four tests were developed to stage the severity of speech/language disorders in PPA patients. All the included studies provided psychometric data about the clinical validity of the tests; however, they present several limitations, both psychometric and methodological. Conclusion : The number of validation studies is still limited. This brief review reveals the need of linguistically sophisticated tests, characterized by better quality of methods and psychometric characteristics, to be used to systematically evaluate the linguistic abilities of individuals with PPA.